A National Evaluation of Internet Crimes Against Children Task Force Training, (United States), 2019-2022 - Boal, Ashley Lynn ([Verlag nicht ermittelbar], 2024)
The Office of Juvenile Justice and Delinquency Prevention (OJJDP)'s Internet Crimes Against Children (ICAC) Training and Technical Assistance (TTA) Program provides TTA to ICAC task force members and their affiliate agencies to support the investigation of ICAC cases. However, little is known about the quality, implementation fidelity, outcomes, and costs associated with ICAC TTA Program training. This study was designed to fill this gap and focused on examining the quality, implementation fidelity, and costs of OJJDP-funded ICAC trainings, as well as participant reactions to training such as perceptions of quality and satisfaction, perceived changes in knowledge and skills, and perceived training results. Using a descriptive design, this study used multiple data collection and analysis approaches, including those that involved extant data collected by TTA providers (i.e., surveys, pre-post tests, implementation data, cost data) and original data collected by the evaluation team (i.e., observations, surveys, interviews, cost data). Findings suggest that overall, ICAC investigative training was rated highly by both trainees and their ICAC commanders in terms of the quality of training delivery, expertise of instructors, knowledge gains, and applicability to on-the-job ICAC investigations. Costs associated with ICAC training suggest a total cost of about USD10.3 million to provide ICAC training over the three-year evaluation period, with annual average costs ranging from USD2.9 million to USD4.3 million over this period. Findings from this study are intended to support OJJDP in its understanding of the ICAC TTA Program to develop and deliver investigative TTA to ICAC task forces.